2007
DOI: 10.1002/qua.21397
|View full text |Cite
|
Sign up to set email alerts
|

Application of the ONIOM (QM/QM) method in the study of molybdena–silica system active in olefin metathesis

Abstract: ABSTRACT:The two-layer ONIOM method is applied for description of Momethylidene center on silica, which is the active site of olefin metathesis. Two clusters of different size are employed to model the silica surface. For the larger one, two differently defined inner layers (the model systems) are tested. In all the calculations, the B3LYP functional is adopted for the inner layer, while the Hartree-Fock method or the local density approximation (SVWN5 functional) is used for the treatment of the real system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…In these reports, both materials were characterized by XAS. The fitted MoO bond lengths (1.70–1.71 Å, Table S2) are consistent with values reported for molecular dioxomolybdates and DFT simulations, ,, as well as the value found in this work (1.68 Å). However, the Mo–O distance reported for the grafted molybdate derived from Mo­(O) 2 [OSi­(O t Bu) 3 ] 2 is longer (1.92 Å) than the corresponding Mo–O paths in silica-supported materials made from Mo­(O)­(O t Bu) 4 and MoO 2 Cl 2 (1.87 and 1.88 Å, respectively).…”
Section: Resultssupporting
confidence: 90%
“…In these reports, both materials were characterized by XAS. The fitted MoO bond lengths (1.70–1.71 Å, Table S2) are consistent with values reported for molecular dioxomolybdates and DFT simulations, ,, as well as the value found in this work (1.68 Å). However, the Mo–O distance reported for the grafted molybdate derived from Mo­(O) 2 [OSi­(O t Bu) 3 ] 2 is longer (1.92 Å) than the corresponding Mo–O paths in silica-supported materials made from Mo­(O)­(O t Bu) 4 and MoO 2 Cl 2 (1.87 and 1.88 Å, respectively).…”
Section: Resultssupporting
confidence: 90%
“…An inner sphere centered at the metal atom and with a radius of ∼6 Å was allowed to relax while keeping the surrounding silica fixed to maintain its amorphous character. Handzlik et al showed that an inner sphere of this size is sufficient to describe the metal site properly. , The calculations were performed with the B3LYP , functional and the D3 dispersion correction . The basis sets used for the various elements were as follows: Def2TZVP and Stuttgart’s pseudopotentials for the metals; 6-31++G­(d,p) for the hydroxyls within the inner sphere and the ammonia molecules; 6-31G­(d) for the remaining atoms in the inner sphere; and 3-21G for the rest.…”
Section: Methodsmentioning
confidence: 99%
“…This limits the quality of the levels of theory that can be employed (e.g., hybrid or double-hybrid functionals are not feasible), so that the accuracy of the energies computed in a mechanistic study may be unreliable. On the other hand, a cluster model of similar size of a PBC simulation cell can be fairly easily treated with better density functionals and larger basis sets, and even higher-level wave function methods through hybrid approaches . Physically, the use of a cluster model is justified because silica is an insulator, and long-range interactions between repeated cells are negligible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dangling bonds were saturated with H [33,34]. Cr(II) species were attached to the (1 0 0) crystal face by replacing two of these H atoms.…”
Section: Methodsmentioning
confidence: 99%